Determinants of potential bankruptcy of companies during the Covid-19 pandemic - Risal Rinofah; Rakotoarisoa Maminaina Heritiana Sedera (Sebelas Maret Business Review, 2022)
The Covid-19 pandemic has had a real and widespread impact on all industries in Indonesia, potentially increasing corporate bankruptcy (financial distress). This study examines the effect of financial ratios on financial distress in various industrial sub-sectors on the Indonesia Stock Exchange during and before the pandemic. The research began with creating a financial distress prediction model using the Logistics Regression Model with monetary and macroeconomic ratio data input during 2016 – 2020. The economic distress prediction model will measure financial distress during the Pandemic and Pre-Pandemic Periods. Empirical testing shows that the pandemic affects the ability of financial ratios to predict bankruptcy. Only the debt ratio and sales growth were significant in predicting bankruptcy during the pre-pandemic period, but cash flow could also expect a default during the pandemic. During a pandemic, sales growth is the most important because it is the aspect most affected by restrictions on consumers' social and economic activities.